2022
DOI: 10.1186/s12882-022-02879-4
|View full text |Cite
|
Sign up to set email alerts
|

Reducing disparities in kidney transplantation for Spanish-speaking patients through creation of a dedicated center

Abstract: Introduction Hispanic Americans receive disproportionately fewer organ transplants than non-Hispanic whites. In 2018, the Hispanic Kidney Transplant Program (HKTP) was established as at the University of Colorado Hospital (UCH). The purpose of this quality improvement study was to examine the effect of this culturally sensitive program in reducing disparities in kidney transplantation. Methods We performed a mixed-methods analysis of data from 436 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…To pass the financial screen, the patient needs to demonstrate the ability to finance insurance copayments after the first calendar year of transplant, when their charity-funded insurance ends . Third, our participants did not report issues with language and culture concordance during the transplant process due to the advent of a culture-concordant transplant center in Colorado, which may not be transferable to other centers.…”
Section: Discussionmentioning
confidence: 99%
“…To pass the financial screen, the patient needs to demonstrate the ability to finance insurance copayments after the first calendar year of transplant, when their charity-funded insurance ends . Third, our participants did not report issues with language and culture concordance during the transplant process due to the advent of a culture-concordant transplant center in Colorado, which may not be transferable to other centers.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study evaluating kidney transplant centers identified only 38 (17%) who provided these non-English language website resources [20]. One center recently reported the implementation of a culturally sensitive transplant program for Spanish-speaking patients, noting a 79% increase in referrals attributed to the program [21]. These data are concordant with referral patterns in language-discordant care among other nontransplant surgical specialties in which non-English speaking patients face barriers to receiving and presenting for referral visits as well as ultimately undergoing the necessary operation [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Further, assisted PD, where a trained caregiver helps patients dialyze, has shown success in alleviating the barriers of limited social support and is reimbursed by healthcare systems in Canada, Denmark, and France [74 ▪ ]. In transplant, culturally concordant transplant education and evaluation has demonstrated an improvement in in disparities among both Black and non-English speaking individuals [75,76 ▪ ,77]. Many programs have also worked to improve delivery of education about home modalities and transplantation to patients [78,79].…”
Section: Potential Solutionsmentioning
confidence: 99%